Quality learning / Sharifah Zannierah Syed Marzuki - Syed Marzuki, Sharifah Zannierah (2003)
Relates higher education to the labour market, noting that the pace of change in national and international economies requires higher education to encourage the development of people who can act effectively in turbulent circumstances. Shows that quality and standards are open to interpretations which depend upon the interpreter's perspective. 'Education' and 'training' must be balanced. The imbalance is harmful to individuals, to industry and to society. A well-balanced education should, of course, embrace analysis and the acquisition of knowledge. It must also include the exercise of creative skills, the competence to undertake and complete tasks and the ability to cope with everyday life and also doing all these things in co-operation with others. List of techniques can be applied to enhance quality learning both to students and educators. On the other hand, it can also increase their motivation.